The Effectivenes of Using Instagram as Online Media toward Writing Descriptive Text at Tenth Grade of Senior High School 8 Jambi City - Silfia, Efa; Rahmawati, Suci (Universitas Batanghari Jambi, 2023)
The popularity of social media between students can be used as a language teaching tool. One of popular is Instagram this is a social network that can be use to take pictures and videos, and share publicly or privately on the application. This study aims to research the effectiveness of using Instagram as a online media toward writing descriptive text. This research was conducted toward the tenth grade of senior high school 8 Jambi city in semester two there were 34 students participated in this test. Seventeen students participated in control class and also seventeen students in experimental class. Based on the researcher findings and discussion, it can be concluded that the use of instagram as online media toward writing descriptive text at the tenth grade of Senior high schoolÂ 8 Jambi City. It was proven by the students mean score improvement from pre-test and post-test. The students mean score of pre test was 36,76. Which was classified as very poor classification, while that of post-test was higher than mean score of pre-test as 53.67 which was classified poor category. Moreover, based on the data analysis, t-test was value. It means that there was a significant difference. Therefore H0 was rejected and H1 was accepted. In other words, the use of instagram as online media toward writing skills students in descriptive text